Diet-induced obesity impairs spermatogenesis: the critical role of NLRP3 in Sertoli cells - Yang Mu; Tai-lang Yin; Yan Zhang; Jing Yang; Yan-ting Wu (BMC, 2022)
Abstract Background Accumulating evidence indicates a key role of Sertoli cell (SC) malfunction in spermatogenesis impairment induced by obesity. Nucleotide-binding oligomerization domain-like receptor with a pyrin domain 3 (NLRP3) is expressed in SCs, but the role of NLRP3 in the pathological process of obesity-induced male infertility remains unclear. Methods NLRP3-deficient mice were fed a high-fat diet for 24 weeks to establish obesity-related spermatogenesis impairment. In another set of experiments, a lentiviral vector containing a microRNA (miR)-451 inhibitor was injected into AMP-activated protein kinase α (AMPKα)-deficient mouse seminiferous tubules. Human testis samples were obtained by testicular puncture from men with obstructive azoospermia whose samples exhibited histologically normal spermatogenesis. Isolated human SCs were treated with palmitic acid (PA) to mimic obesity model in vitro. Results Increased NLRP3 expression was observed in the testes of obese rodents. NLRP3 was also upregulated in PA-treated human SCs. NLRP3 deficiency attenuated obesity-related male infertility. SC-derived NLRP3 promoted interleukin-1β (IL-1β) secretion to impair testosterone synthesis and sperm performance and increased matrix metalloproteinase-8 (MMP-8) expression to degrade occludin via activation of nuclear factor-kappa B (NF-κB). Increased miR-451 caused by obesity, decreased AMPKα expression and sequentially increased NADPH oxidase activity were responsible for the activation of NLRP3. miR-451 inhibition protected against obesity-related male infertility, and these protective effects were abolished by AMPKα deficiency in mice. Conclusions NLRP3 promoted obesity-related spermatogenesis impairment. Increased miR-451 expression, impaired AMPKα pathway and the subsequent ROS production were responsible for NLRP3 activation. Our study provides new insight into the mechanisms underlying obesity-associated male infertility.